Nurse Competence, Work Environment, and Patient Safety: The Mediating Role of Bedside Handover in Indonesia: A Cross-Sectional Study - Kaparang, Sova Nova; Putra, Kuswantoro Rusca; Kapti, Rinik Eko (Chakra Brahmanda Lentera Institute, 2026)
Background: Patient safety remains a major global concern, especially in low- and middle-income countries (LMICs) where resource limitations and communication gaps contribute to preventable harm. Although bedside handover is recognized as a strategy to enhance transparency and safety culture, few studies have examined its mediating role between nurse competence, work environment, and patient safety. Methods: This cross-sectional study, conducted in accordance with STROBE guidelines, involved 258 inpatient nurses selected through proportionate stratified random sampling from four hospitals in North Sulawesi, Indonesia. Eligible participants had at least one year of experience and were actively involved in bedside handover. Validated instruments the Nurse Competence Scale (NCS), Area of Worklife Survey (AWS), Nursing Handoff Competency Scale (NHCS), and Safety Care Activity Scale (SCAS), were used. Structural Equation Modeling with Partial Least Squares assessed measurement validity and structural relationships. Results: All instruments met recommended validity and reliability standards, and the sample primarily comprised early-career female nurses. Structural modeling showed that both nurse competence and the work environment were positively associated with bedside handover, which in turn demonstrated a strong relationship with patient safety. Bedside handover partially mediated the influence of nurse competence and fully mediated the influence of the work environment on patient safety. Conclusion: Bedside handover serves as a central mechanism linking individual capabilities and organizational conditions to safer patient outcomes. Strengthening competency development, promoting fairness and teamwork, and standardizing bedside handover practices may offer practical, low-cost pathways to improve patient safety in LMIC contexts